2019
DOI: 10.1007/s40264-019-00835-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Safety of Prucalopride in Patients with Chronic Constipation: A Multinational Population-Based Cohort Study

Abstract: IntroductionThe serotonin 5-HT4 receptor agonist prucalopride is approved in the European Union for the treatment of chronic constipation. This offered the unique opportunity to include real-world observational data on cardiovascular safety in the new drug application for approval of prucalopride in the USA.MethodsThis observational population-based cohort study (EUPAS9200) conducted in five data sources (three in the UK, one in Sweden, and one in Germany [which was subsequently excluded from the pooled analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 7 publications
1
35
0
Order By: Relevance
“…18,22 However, a recent observational population-based cohort study showed that the pooled adjusted incidence rate ratio of major adverse cardiovascular events comparing new use of prucalopride with new use of polyethylene glycol 3350 was 0.64 (95%CI, 0.36-1.14). 23 Based on the results, the slight increase of HR by prucalopride would not induce major adverse cardiovascular events. Heart rate tachycardic outliers 0 0 0 0 Heart rate bradycardic outliers, 0 0 0 0 PR outliers, n (%) 1 As for TEAEs, no cardiovascular TEAE occurred.…”
Section: Discussionmentioning
confidence: 93%
“…18,22 However, a recent observational population-based cohort study showed that the pooled adjusted incidence rate ratio of major adverse cardiovascular events comparing new use of prucalopride with new use of polyethylene glycol 3350 was 0.64 (95%CI, 0.36-1.14). 23 Based on the results, the slight increase of HR by prucalopride would not induce major adverse cardiovascular events. Heart rate tachycardic outliers 0 0 0 0 Heart rate bradycardic outliers, 0 0 0 0 PR outliers, n (%) 1 As for TEAEs, no cardiovascular TEAE occurred.…”
Section: Discussionmentioning
confidence: 93%
“…Anorectal biofeedback, nerve stimulation, and colonic surgery may be used to treat FC [9][10][11]. Although there are many methods to choose from, the side effects of these methods are notable, including diarrhea, bloating, nausea, and possible cardiovascular adverse events [12][13][14]. As a result, many people, including those who do not improve with existing medications or suffer many side effects, are interested in complementary alternative medicine.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of a multinational, multi-database study using a common protocol to evaluate the occurrence of major adverse cardiovascular events (MACE) among initiators of prucalopride and initiators of polyethylene glycol (PEG), the aim of this manuscript is to show the performance of propensity score (PS) stratification and trimming to obtain comparable study cohorts; and to report study design decisions undertaken when balance could not be achieved. The findings in terms of MACE of the prucalopride safety study are reported elsewhere [5].…”
Section: Introductionmentioning
confidence: 87%
“…Finally, the deciles of the PS were derived, and balance of the potential confounding factors between cohorts was checked. Stratification on the deciles of the PS was used to obtain adjusted estimates for the main study [5]. For each data source, the following characteristics of all variables of interest were described for each cohort after trimming: for categorical variables, the frequency (i.e.…”
Section: Methodsmentioning
confidence: 99%